A PRISMA systematic review of adolescent gender dysphoria literature: 3) treatment. - Lucy Thompson; Darko Sarovic; Philip Wilson; Louis Irwin; Dana Visnitchi; Angela Sämfjord; Christopher Gillberg (Public Library of Science (PLoS), 2023)
It is unclear whether the literature on adolescent gender dysphoria (GD) provides evidence to inform clinical decision making adequately. In the final of a series of three papers, we sought to review published evidence systematically regarding the types of treatment being implemented among adolescents with GD, the age when different treatment types are instigated, and any outcomes measured within adolescence. Having searched PROSPERO and the Cochrane library for existing systematic reviews (and finding none at that time), we searched Ovid Medline 1946 -October week 4 2020, Embase 1947-present (updated daily), CINAHL 1983-2020, and PsycInfo 1914-2020. The final search was carried out on 2nd November 2020 using a core strategy including search terms for 'adolescence' and 'gender dysphoria' which was adapted according to the structure of each database. Papers were excluded if they did not clearly report on clinically-likely gender dysphoria, if they were focused on adult populations, if they did not include original data (epidemiological, clinical, or survey) on adolescents (aged at least 12 and under 18 years), or if they were not peer-reviewed journal publications. From 6202 potentially relevant articles (post deduplication), 19 papers from 6 countries representing between 835 and 1354 participants were included in our final sample. All studies were observational cohort studies, usually using retrospective record review (14); all were published in the previous 11 years (median 2018). There was significant overlap of study samples (accounted for in our quantitative synthesis). All papers were rated by two reviewers using the Crowe Critical Appraisal Tool v1·4 (CCAT). The CCAT quality ratings ranged from 71% to 95%, with a mean of 82%. Puberty suppression (PS) was generally induced with Gonadotropin Releasing Hormone analogues (GnRHa), and at a pooled mean age of 14.5 (±1.0) years. Cross Sex Hormone (CSH) therapy was initiated at a pooled mean of 16.2 (±1.0) years. Twenty-five participants from 2 samples were reported to have received surgical intervention (24 mastectomy, one vaginoplasty). Most changes to health parameters were inconclusive, except an observed decrease in bone density z-scores with puberty suppression, which then increased with hormone treatment. There may also be a risk for increased obesity. Some improvements were observed in global functioning and depressive symptoms once treatment was started. The most common side effects observed were acne, fatigue, changes in appetite, headaches, and mood swings. Adolescents presenting for GD intervention were usually offered puberty suppression or cross-sex hormones, but rarely surgical intervention. Reporting centres broadly followed established international guidance regarding age of treatment and treatments used. The evidence base for the outcomes of gender dysphoria treatment in adolescents is lacking. It is impossible from the included data to draw definitive conclusions regarding the safety of treatment. There remain areas of concern, particularly changes to bone density caused by puberty suppression, which may not be fully resolved with hormone treatment.